Artificial intelligence and placental DNA methylation: newborn prediction and molecular mechanisms of autism in preterm children. (12th December 2022) - Bahado-Singh, Ray O.; Vishweswaraiah, Sangeetha; Aydas, Buket; Radhakrishna, Uppala
Abstract: Background: Autism Spectrum Disorder (ASD) represents a heterogeneous group of disorders with a complex genetic and epigenomic etiology. DNA methylation is the most extensively studied epigenomic mechanism and correlates with altered gene expression. Artificial intelligence (AI) is a powerful tool for group segregation and for handling the large volume of data generated in omics experiments. Methods: We performed genome-wide methylation analysis for differential methylation of cytosine nucleotide (CpG) was performed in 20 postpartum placental tissue samples from preterm births. Ten newborns went on to develop autism (Autistic Disorder subtype) and there were 10 unaffected controls. AI including Deep Learning (AI-DL) platforms were used to identify and rank cytosine methylation markers for ASD detection. Ingenuity Pathway Analysis (IPA) to identify genes and molecular pathways that were dysregulated in autism. Results: We identified 4870 CpG loci comprising 2868 genes that were significantly differentially methylated in ASD compared to controls. Of these 431 CpGs met the stringent EWAS threshold ( p -value <5 × 10 −8 ) along with ≥10% methylation difference between CpGs in cases and controls. DL accurately predicted autism with an AUC (95% CI) of 1.00 (1–1) and sensitivity and specificity of 100% using a combination of 5 CpGs [cg13858611 ( NRN1 ), cg09228833 ( ZNF217 ), cg06179765 ( GPNMB ), cg08814105 ( NKX2-5 ), cg27092191 ( ZNF267 )] CpG markers. IPA identified five prenatally dysregulated molecular pathways linked to ASD. Conclusions: The present study provides substantial evidence that epigenetic differences in placental tissue are associated with autism development and raises the prospect of early and accurate detection of the disorder.